1998
DOI: 10.1094/cchem.1998.75.5.595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exogenous Lipase on Dough Lipids During Mixing of Wheat Flours

Abstract: Cereal Chem. 75(5):595-601In control dough, endogenous wheat lipase was inactive, because the triacylglycerol (TAG), 1,2-diacylglycerol (DAG 1,2 ), and 1,3-diacylglycerol (DAG 1,3 ) fractions of nonpolar lipids were not affected by mixing. Conversely, the free fatty acid (FFA) and monoacylglycerol (MAG) fractions decreased, mainly due to the oxidation of polyunsaturated fatty acids (PUFA) catalyzed by wheat lipoxygenase. Addition of exogenous lipase to flour (15 lipase units [LU] per gram of dry matter) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
4
31
0
4
Order By: Relevance
“…These hydroperoxides, and intermediary free radicals formed during mixing, can co-oxidize several compounds -and are often transformed into a variety of aldehydes and oxygenated FA. Furthermore, endogenous lipases -which hydrolyze TAG, DAG, and MAG of NL fractions, will consequently lead to increases in MAG and FA fractions [56,57].…”
Section: (Esi-ms-msmentioning
confidence: 99%
“…These hydroperoxides, and intermediary free radicals formed during mixing, can co-oxidize several compounds -and are often transformed into a variety of aldehydes and oxygenated FA. Furthermore, endogenous lipases -which hydrolyze TAG, DAG, and MAG of NL fractions, will consequently lead to increases in MAG and FA fractions [56,57].…”
Section: (Esi-ms-msmentioning
confidence: 99%
“…Undoubtedly, lipase functionality comprises several aspects (Castello et al 2000, Poulsen andBorch Sse 1997). By analyzing the biochemical changes induced by the exogenous lipases, Castello et al (1998Castello et al ( , 2000 proposed a more indirect impact of lipases on the gluten. At the same time, the level of emulsifying molecules increases, which may result in an increased stability of the gas cells (Castello et al 1998(Castello et al , 2000.…”
Section: Lipasesmentioning
confidence: 99%
“…Phospholipids can impact on breadmaking quality, though not individually, as it has been shown that there appears to be synergistic effects in phospholipid mixtures that most strongly affect loaf volume (Helmerich and Koehler, 2005). Modifi cation of the lipids by lipase (Castello et al , 1998) has been found to improve the breadmaking properties (Weegels and Hamer, 1992), suggesting that the foaming activity of the intrinsic lipids has considerable room for improvement. In general, the foaming properties of the non-polar lipids similar to those present in wheat are not particularly good.…”
Section: Lipidsmentioning
confidence: 99%
“…The balance of foaming and non-foaming lipids is likely to be infl uenced by wheat variety, environmental conditions and processing conditions (including milling) (Morrison and Barnes, 1983). Lipases have been used to hydrolyse di-and tri-acyl lipids into monoglycerides and lysolipids (Castello et al , 1998); this has increased loaf volumes and crumb structure, and has been offered as a replacement for emulsifi ers (Weegels and Hamer, 1992;Monfort et al , 1999). The effect is probably based on the fact that the hydrolysis products are more soluble, surface active and foam active than the substrate lipids, and lower the surface tension more effectively (Primo-Martin et al , 2006).…”
Section: Added Ingredientsmentioning
confidence: 99%